Case report: Two individuals with AEBP1-related classical-like EDS: Further clinical characterisation and description of novel AEBP1 variants - Angwin, Chloe; Ghali, Neeti; van Dijk, Fleur Stephanie (Frontiers in Genetics, 2023)
Introduction AEBP1 related classical like EDS (clEDS type 2) is a rare EDS type, first reported in 2016. There are overlapping clinical features with TNXB related classical like EDS (or clEDS type 1) including skin hyperextensibility, joint hypermobility and easy bruising. There are currently 9 reported individuals with AEBP1- related clEDS type 2. This report confirms previous findings and provides additional clinical and molecular data on this group of individuals. Materials and methods Two individuals (P1 and P2) with features of a rare type of EDS were clinically assessed in the London national EDS service and underwent genetic testing Results Genetic testing in P1 revealed likely pathogenic AEBP1 variants: c.821del:p.(Pro274Leufs*18) and c.2248T>C:p.(Trp750Arg). In P2 pathogenic AEBP1 variants c.1012G>T:p.(Glu338*) and c.1930C>T:p.(Arg644*) were identified. Discussion These two individuals bring the reported number of individuals with AEBP1-related clEDS to 11 (6 females, 5 males). There are shared features with previously reported individuals including hypermobility (11/11), skin hyperextensibility (11/11), presence of atrophic scarring (9/11) and easy bruising (10/11). In P1 a chronic right vertebral artery dissection, mild dilatation of the splenic artery, aberrant subclavian artery and tortuous iliac arteries were noted at the age of 63 years. Cardiovascular disease has been reported: mitral valve prolapse (4/11), peripheral arterial disease (1/11) and aortic root aneurysm requiring surgical intervention (1/11). Hair loss has been reported in 6/11 individuals (5 females, 1 male), only 1 of which was documented to have a formal diagnosis of androgenetic alopecia, while other individuals are described as having thinning of hair, male pattern hair loss or unspecified alopecia. Conclusion The clinical features of individuals with AEBP1 related EDS have not yet been fully elucidated. Hair loss is present in 6/11 individuals with AEBP1 related clEDS and as such appears to be a feature of this condition. This is the first time hair loss has been formally reported as a characteristic feature in a rare type of EDS. Cardiovascular surveillance seems warranted in this condition due to 2/11 individuals having evidence of arterial aneurysm and/or dissection. Further descriptions of affected individuals are necessary to inform diagnostic criteria and management guidelines.